Surface adherence properties and antimicrobial susceptibility of coagulase negative staphylococci with intrahospital and community origin. - Labachevska Gjatovska, Liljana; Pavlovska, Kristina; Cekovska, ZHaklina (Macedonian Association of Anatomists and Morphologists (MAAM), 2021)
Introduction: Coagulase-negative staphylococci (CoNS) were long regarded harmless commensals which commonly colonize human skin and mucous membranes. Although CoNS are usually in a benign relationship with the host, changes in the medical practice and also in the underlying host populations resulted in their emerge as opportunistic pathogens with key role primarily in nosocomial but in community-acquired infections as well. Objective: Тo determine the association between surface adherence properties/ antimicrobial susceptibility and the isolates origin in clinically significant CoNS and CoNS from normal skin microbiota of healthcare workers and healthy volunteers. Material and methods: CoNS were identified by sample cultivation on standard microbiological nutrition media, gram staining and biochemical tests. Modification of the microtiter plate assay described by Christensen et al. was used to investigate the formation of biofilm. The antimicrobial susceptibility testing (AST) was performed according to EUCAST standard disc diffusion method guidelines for 13 drugs frequently prescribed as commonly active against CoNS. Results: In present study biofilm production was observed in 9 (90%), 7 (70%) and 2 (20%) CoNS isolates from blood cultures from septic patients, skin swabs from hands of medical professionals and skin samples from hands of healthy volunteers, accordingly. Importantly, our study indicated that 63.3% CoNS isolates were resistant to methicillin. Along with the resistance to methicillin, a multidrug resistance pattern towards benzylpenicillin (63.3%), flucloxacillin (63.3%), ceftriaxone (63.3%) and cefotaxime (63.3%) was noted. The results obtained in the study also showed that, the biofilm forming coagulase negative staphylococci have higher resistance rates to various antibiotics compared to biofilm non- producing bacteria. Conclusion: Highest production of biofilm and multidrug resistance were observed in bacterial isolates obtained from hospital environment. We also observed that the majority of MDR pathogens were biofilm producers and were almost equally present in blood samples from critical patients and skin samples of the hands of healthcare personnel.
Keywords: biofilm production; coagulase negative Staphylococcus; antimicrobial resistance